ANTARA ZUHUD DAN KRITIK KEKAYAAN: KONSTRUKSI MAKNA "CINTA DUNIA" DALAM DAKWAH GUS BAHA DAN GUS ULIL DI MEDIA BARU - Muhamad Ibtissam Han (Raqib: Jurnal Studi Islam, 2026)
This article examines how preachers of Nahdlatul Ulama (NU) construct the meaning of "worldliness" (hubbud al-dunya) within the context of contemporary digital Islamic preaching in Indonesia, focusing on two prominent figures: K.H. Ahmad Bahauddin Nursalim (Gus Baha) and K.H. Ulil Abshar Abdalla (Gus Ulil). Amid the growing prominence of prosperity preaching — a mode of religious communication that implicitly or explicitly links piety with material success — both figures have emerged as significant counter-narratives rooted in the Aswaja Sufi tradition. This study employs a qualitative approach utilizing Norman Fairclough's three-dimensional Critical Discourse Analysis (CDA). Primary data were gathered through semi-structured interviews with Gus Ulil  and systematic observation of Gus Baha's sermon content on the YouTube channels Santri Gayeng and LP3IA Official (April–May 2024). The findings reveal that both figures construct markedly different meanings: Gus Baha articulates his anti-worldliness through what this article terms performative asceticism — a lived zuhud (renunciation) embodied in his lifestyle and functioning as a symbolic token of religious authority in digital space — while Gus Ulil offers a critical textual reinterpretation, reading Al-Ghazali's Kitab Dhamm al-Dunya not as a call to literal asceticism, but as a critique of wealth relevant to contemporary materialism. Despite their divergent strategies, both figures share the same traditional roots and function as complementary entry points into Aswaja Sufi ethics, reaching different but overlapping audiences. These findings demonstrate that the NU tradition possesses rich internal resources capable of responding adaptively to consumerism and the commodification of religion in the digital age, while also revealing that religious authority in the digital era is not solely determined by platform mastery.